Avian reticuloendotheliosis virus: characterization of the high-molecular-weight viral RNA in transforming and helper virus populations. - Gonda, M A (1980)
Reticuloendotheliosis virus strain T (REV-T) is a type C retrovirus known to transform avian fibroblasts, spleen cells, and bone marrow cells and to produce virulent reticuloendotheliosis in young chicks. Analysis of REV-T high-molecular-weight RNA by electrophoresis in denaturing gels and by electron microscopy revealed the presence of at least two classes of molecules. One class appeared in CH3HgOH gels to have a monomer length of 9.3 kilobases (kb); in electron microscopic spreads under mildly denaturing conditions, it existed as a typical retrovirus dimer, having a monomer length of 8.8 +/- 0.7 kb. The second class also existed as a dimer, with a monomer length of 5.7 kb in CH3HgOH gels. Hybridization with REVA-A 32P-labeled complementary DNA revealed a third size class of molecules (4.7 kb), which were not resolvable from the 5.7-kb class in electron microscope spreads and which comigrated with chicken 28S rRNA in denaturing gels. Only the 9.3-kb class was found in the reportedly nontransforming virus produced after infection of canine thymus cell line with REV-T. Thus, REV-T appears to be similar to the murine and feline sarcoma viruses and the avian acute leukemia viruses in that it consists of a nontransforming helper virus genome and a defective genome responsible for oncogenicity. Our previous results demonstrated the presence in REV-T and in uninfected chicken cellular DNA of some nucleotide sequences not found in virus produced by the canine line (S. Simek and N. Rice, J. Virol. 33:320--329, 1980). In this report we show by hybridization with highly specific 32P-labeled complementary DNAs that REV-T-specific sequences exist within the 5.7-kb genome. Since 32P-labeled complementary DNA synthesized from the canine-derived virus genome hybridized with all three classes of RNAs, we conclude that the 5.7-kb genome is a recombinant between some sequences found in the putative helper and some sequences specific to REV-T. As with the other oncogenic viruses mentioned above, these specific sequences appear to be derived from host DNA.